ANALISA KERUSAKAN FORMASI PADA SUMUR INJEKSI H-01, H-02, H-03 & H-04 MENGGUNAKAN METODE HALL PLOT PADA LAPANGAN KENARI - Hendra Budiman; Erik Triansyah (Jurnal Cakrawala Ilmiah, 2023)
Water injection is one of the secondary recovery stages used to increase oil and gas production. In its application, injected water is prone to cause problems such as damage to the formation, therefore it is necessary to analyze, including using the Hall Plot method. The Hall Plot method is a curve plotted based on cumulative pressure against cumulative injection volume, where this method is used to identify what the actual condition of the injection well is. From the results of the analysis and calculations that have been carried out on the four injection wells, one of them is experiencing formation damage, namely the H-01 well, as seen from the results of the calculation of the Skin factor from the Darcy and Hall Plot formulations showing a value of +32.011 and +64.562 and the value of the Injectivity Index is 2.026 bbl/day/Psi. Wells that have been identified as damaged are then analyzed for stimulation feasibility. From the results of the stimulation feasibility analysis in the form of injection water quality analysis and calculations, it is recommended that the H-01 well be matrix acidizing